Safety and efficacy of remote ischemic conditioning in adult moyamoya disease patients undergoing revascularization surgery: a pilot study - Yang, Heng; Hu, Zhenzhen; Gao, Xinjie; Su, Jiabin; Jiang, Hanqiang; Yang, Shaoxuan; Zhang, Qing; Ni, Wei; Gu, Yuxiang (Frontiers in Neurology, 2023)
Background and purpose: Revascularization surgery for patients with moyamoya disease (MMD) is very complicated and has high rate of postoperative complications.This pilot study aimed to prove the safety and efficacy of remote ischemic conditioning (RIC) in adult MMD patients undergoing revascularization surgery Methods: 44 patients with MMD were enrolled in this single-center, open-label, prospective, parallel randomized study, including 22 patients assigned to sham group and 22 patients assigned to RIC group. The primary outcome was the incidence of major neurologic complications during perioperative period. Secondary outcomes were the Modified Rankin Scale (MRS) score at discharge, at 90 days post-operation and at 1 year after operation. The outcome of safety was the incidence of adverse events associated with RIC. Blood samples were obtained to monitoring that the serum concentrations of cytokines (VEGF, IL-6).No subjects experienced adverse events during RIC intervention and all patients can tolerate to the RIC intervention in perioperative period. The incidence of major neurologic complications was significantly lower in the RIC group compared with the control group (18.2% vs 54.5%, P=0.027). The mRS score at discharge in the RIC group was also lower than control group (0.86±0.99 vs 1.18±1.22, P=0.035). In addition, the serum IL-6 level increased significantly at 7 days after bypass surgery in control group and the serum level of VEGF at 7 days post-operation in the RIC group.In conclusion, our study demonstrated the neuroprotective effect of RIC by reducing peri-operative complications and improving cerebral blood flow in adult MMD patients undergoing revascularization surgery. Thus, RIC seems to be a potential treatment method for MMD.